DAMPAK PEMBIAYAAN INVESTASI DENGAN UTANG DAN JAMINAN DARI MODAL SENDIRI (Case Study PT Agung Podomoro Land Tbk) - Akhmad, Akhmad; Kadir, Abdul; Djalamang, Zulfikar Jakaputera; Hasan, Hasan (Jurnal Ekonomi Trend, 2021)
This study aims to recommend decision making related to the use of debt in corporate financing. This study took data from PT Agung Podomoro Land Tbk. In addition to developing, the company also plays a role in providing modern residential facilities. This study focuses on the financing structure between debt and equity. The results of the study become an important study to see the company's performance through the LTDER ratio with the use of 2017-2019 data. The results of the study found that there was a large percentage of debt financing carried out by companies from 2017 to 2019. This condition indicates that debt financing makes a greater contribution than own capital to funding and business growth. Keywords: Financing, Long-Term Debt, Equity